(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Organ transplantation is a life-saving procedure for many patients. However, every year a large number of patients die on the waiting lists due to the shortage of available organs. Thus the organ scarcity problem has been the starting point for reflecting on the effectiveness of the current transplantation system based on willingness to donate and altruism. The analysis of the evolution of the Italian transplantation discipline gives the opportunity to focus on the reform perspectives of the organ procurement system aimed at changing the consent mechanism and the prohibition of organ commercialization. In the recent years, the debate on the scarcity problem has shift from those traditional perspectives to a new one that includes heterogeneous ways to reduce the shortage of organs such as the use of marginal donors, the crossover technique and the reciprocity principle for organ allocation.